2018
DOI: 10.1007/s11999.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Are Age and Patient Gender Associated With Different Rates and Magnitudes of Clinical Improvement After Reverse Shoulder Arthroplasty?

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 16 publications
(27 reference statements)
3
43
0
Order By: Relevance
“…Leathers et al 16 showed better range of motion and improvement in range of motion in younger patients, whereas the ASES score was not different from that in older patients at final review. Furthermore, Friedman et al 10 analyzed an international database of 660 RSA patients with a mean age of 72 years. They found that each 1-year increase was associated with an improved ASES score by 0.19 points ( P = .006) but with decreased forward flexion by 0.39° ( P = .001) per year.…”
Section: Discussionmentioning
confidence: 99%
“…Leathers et al 16 showed better range of motion and improvement in range of motion in younger patients, whereas the ASES score was not different from that in older patients at final review. Furthermore, Friedman et al 10 analyzed an international database of 660 RSA patients with a mean age of 72 years. They found that each 1-year increase was associated with an improved ASES score by 0.19 points ( P = .006) but with decreased forward flexion by 0.39° ( P = .001) per year.…”
Section: Discussionmentioning
confidence: 99%
“…Factors including age, sex, smoking, and BMI are known to be related to the magnitude of clinical improvement after RTSA. 9 , 11 , 27 , 31 , 37 On the basis of the effect of obesity on the clinical outcomes of RTSA, increased body weight was significantly associated with deep infection after RTSA. 1 In our study, the overwhelming female majority made it difficult to identify negative effects on male patients.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize selection bias from patient-related factors, which have been revealed to affect the outcomes of CTA or ICTs in RTSA, multiple factors, including patients' age, sex, and body mass index (BMI), were considered. 1 , 9 , 11 , 22 , 27 , 31 , 37 Propensity score (PS) matching was used to obtain reliable information by considering factors known to affect the clinical outcomes of RTSA. PS matching at a 1:2 ratio was performed based on the patients' age, sex, and BMI through logistic regression.…”
Section: Methodsmentioning
confidence: 99%
“…Successful outcomes of anatomic total shoulder arthroplasty (aTSA) and reverse total shoulder arthroplasty (rTSA) are well documented in the literature 1 , 7 , 8 , 18 , 23, 24, 25. However, concerns exist regarding the variability of results, such as the unpredictable improvement in internal and external rotation after rTSA 7 , 26 , 27 .…”
mentioning
confidence: 99%
“…Successful outcomes of anatomic total shoulder arthroplasty (aTSA) and reverse total shoulder arthroplasty (rTSA) are well documented in the literature 1 , 7 , 8 , 18 , 23, 24, 25. However, concerns exist regarding the variability of results, such as the unpredictable improvement in internal and external rotation after rTSA 7 , 26 , 27 . Although several associations for total shoulder arthroplasty (TSA) have been previously identified, such as preoperative diagnosis, 4 , 28 weak deltoid function, 3 depression, 29 , 30 sex, 7 , 22 body mass index (BMI), 2 , 9 , 14 , 15 , 17 medical comorbidities, 21 and patient age at the time of surgery, 5 , 7 , 10 the contribution of each to different postoperative outcome measures is unknown.…”
mentioning
confidence: 99%